2022
DOI: 10.1177/08839115221121844
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on salicylic acid-based poly(anhydride-ester): Implications for polymer degradation and controlled salicylic acid release

Abstract: Salicylic acid (SA)-based poly(anhydride-esters) (SAPAEs) hydrolytically degrade to release SA in a controlled manner over extended time periods. While these polymers have been well investigated under in vivo conditions, this study is the first detailed, systematic assessment of in vitro polymer degradation over a range of pH values. To investigate the effect of pH conditions on SAPAE degradation, in vitro degradation studies were conducted on SAPAE disks over a wide pH range (2.0, 4.0, 6.0, 7.4, 8.0, 9.0, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…As expected, variation of the NaOH concentration could be used to vary mass loss in all species, which indicates that the degradation mechanism is purely hydrolytic (Figure , SI Figure 24). Most importantly, by these degradation studies we confirmed the release of salicylic acid derivatives in all cases through spectroscopy, with more prolonged release demonstrated by our materials compared with other PolyAspirins and encapsulated/incorporated forms of salicylic acid. ,, ,, The degradation also follows a surface erosion process, as confirmed through optical observations of film erosion (SI Figure 25) as well as of porous structures over time as well as through more complex drug release studies. Through selection of the linker species, the daily released concentration could be varied while maintaining linear release profiles over time.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…As expected, variation of the NaOH concentration could be used to vary mass loss in all species, which indicates that the degradation mechanism is purely hydrolytic (Figure , SI Figure 24). Most importantly, by these degradation studies we confirmed the release of salicylic acid derivatives in all cases through spectroscopy, with more prolonged release demonstrated by our materials compared with other PolyAspirins and encapsulated/incorporated forms of salicylic acid. ,, ,, The degradation also follows a surface erosion process, as confirmed through optical observations of film erosion (SI Figure 25) as well as of porous structures over time as well as through more complex drug release studies. Through selection of the linker species, the daily released concentration could be varied while maintaining linear release profiles over time.…”
Section: Resultssupporting
confidence: 73%
“…Several studies have used salicylic acid as building blocks for either soft thermoset materials displaying low strains at failure of approximately 20% during uniaxial tensile testing or functional polymers with temporal components in their design (4D polymers). , Notably, the Uhrich group has contributed a large body of work developing PolyAspirin, attempting to leverage polymer design to overcome the aforementioned drug delivery loading limitations where salicylic acid is directly incorporated into the polymer backbone to serve as a therapeutic agent upon release. ,,,, While the release profiles of this work are promising with regard to sustained release greater than 24 h and ∼45% loading of the salicylic acid (the highest to date), a significant limitation with this technique is the difficulties with processing these materials into geometries which may be of clinical use and extending the release times past ∼60 days. ,,, Recently, this work has focused on making the materials more processable, including developing extrudable formulations, which unfortunately required lowered the salicylic acid concentration in the polymer backbone to achieve greater flow . Other attempts at incorporating salicylic acid have focused on leveraging salicylic acid in the polymer backbone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation